THE ROLE OF COMPOUNDS BASED ON HYDROLYZED PROTEIN IN PROPHYLAXIS AND DIET TREATMENT OF ALIMENTARY ALLERGY IN INFANTS - T.E. Borovik; S.G. Makarova; S.N. Darchiya; A.V. Gamaleyeva ("Paediatrician" Publishers LLC, 2010)
Alimentary allergy in infants occurs because of intolerance to the cow's milk protein. Infant formulas with hydrolyzed protein are widely used for the prophylaxis and treatment of alimentary allergy in children. The article describes main peculiarities and principles of administration of hypoallergenic infant formulas and formulas based on hydrolyzates of serum proteins or casein. Special attention is given to the nutrients' role (nucleotides, long-chain polyunsaturated fatty acids), included into hypoallergenic formulas. The peculiarities and terms of supplementary feeding introduction in patients with alimentary allergy are discussed.  Key words: children, alimentary allergy, hypoallergenic formulas, nucleotides, oligosaccharides. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):150-156)